The networked reception of transmedial universes: An experience-centered approach - Tosca, Susana; Klastrup, Lisbeth (MedieKultur: Journal of media and communication research, 2016)
Building upon ten years of empirical work, this paper reflects on how to study increasingly complex user engagement with transmedial worlds. We examine our own analytical evolution from an initial aesthetic orientation to our current effort to incorporate the user´s own perspective through qualitative and quantitative studies. We argue that mapping user experience requires a sophisticated and holistic analytical approach - particularly, due to the popularity of social media platforms. We conclude the article by developing the concept of "networked reception" to characterize new kinds of transmedial world experience afforded by social media, which allow users to distribute and communicate not only the content of media texts but also their own experience and reception of transmedial world “texts”.